(untitled) (Research, Society and Development, 2021)
The growth of plants, their development and functioning within their habitat is studied by the area of ​​Biology called Plant Physiology. In high school, this area is seen by students as complex and tedious, as it has many processes and terms that must be very well contextualized. In order to overcome such problems, the present work has as main objective to facilitate and instigate students’ learning in the discipline of Biology, in High School, more precisely within Plant Physiology, regarding the topic of water absorption and transport in angiosperms by means of of a simple and low-cost experiment using young common Bean plants (Phaseolus vulgaris L.) as a model. Thus, the practical activity in question allows to promote a greater interest of the students, facilitating the contextualization besides allowing the work of the scientific experimentation, being a task of great impact of the teaching process.